INTEGRASI MODEL PEMBELAJARAN PBL DAN NHT BERBANTUAN MEDIA TTS DALAM MENINGKATKAN HASIL BELAJAR - Izza Milenia Ariyati; Riza Yonisa Kurniawan (Jurnal PROFIT: Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2023)
Learning still makes the teacher the center of information so that only 14% of student learning outcomes are complete and 86% are incomplete. This research was conducted to improve student learning outcomes on the concept of business entities by implementing the integration of Problem Based Learning (PBL) and Numbered Head Together (NHT) learning models assisted by Crossword Puzzles (TTS) media. This research is a Classroom Action Research (CAR) which was carried out in two cycles. The subjects in this study were students of class X IPA 7 at SMAN 1 GEDEG. Based on the results of the research, the application of model integration, in cycle I, students who passed increased to 31% and did not complete decreased to 69% until in cycle II, students who completed increased to 100% and those who did not complete 0%. The application of the integration of the Problem Based Learning and Numbered Head Together learning models with the help of Crosswords media can improve student learning outcomes with the subject of the Business Entity Concept in the subject of Economics in class X IPA 7 SMAN 1 Gedeg